VARIASI PENAMBAHAN GULA MERAH AREN (Arenga pinnata) DENGAN KONSENTRASI BERBEDA PADA DENDENG IKAN SEPAT SIAM (Trichogaster pectoralis) TERHADAP PENERIMAAN PANELIS - Candra Candra; Rabiatul Adawyah; Mawarti Mawarti (Faculty of Fisheries and Marine Resources of Lambung Mangkurat University-South Kalimantan, 2017)
Dendeng sepat siam is a semi-wet processed with curing in spice solution (onion, garlic, palm sugar, salt, water, galangal, coriander, and tamarind). The purpose of this study was to determine the concentration of palm sugar (Arengapinnata) on the processing of dendeng sepat siam (Trichogaster pectoralis). This study uses organoleptic tests that include color, aroma, texture, and taste. The results showed that addition of different palm sugar concentration affect the aroma and color specifications, but not havean effect on texture and taste. The best treatment is the 24% addition of palm sugar.